2014
DOI: 10.1111/bju.12743
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery after energy ablation for renal masses

Abstract: ObjectivesTo evaluate the feasibility, safety, pathological, radiological and functional outcomes of salvage surgery after previous renal mass ablation therapy. Patients and MethodsAfter institutional review board approval, we reviewed our renal tumour database, and described the characteristics and outcomes of patients who experienced a local recurrence after energy ablation for renal masses and underwent salvage surgical therapy. ResultsA total of 14 patients fit the inclusion criteria. The median (interquar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In an analysis of 337 recurrent CA cases, Long and Park reported a salvage nephrectomy rate of 2.4% [83]. Surgery is complicated by desmoplastic reaction in the perinephric tissue, which has been reported to be more dense after LCA than is observed after failed PCAs or LPN with a higher risk of major complications [34,35].…”
Section: Salvage Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of 337 recurrent CA cases, Long and Park reported a salvage nephrectomy rate of 2.4% [83]. Surgery is complicated by desmoplastic reaction in the perinephric tissue, which has been reported to be more dense after LCA than is observed after failed PCAs or LPN with a higher risk of major complications [34,35].…”
Section: Salvage Optionsmentioning
confidence: 99%
“…The search returned a total of 11 noncomparative CA studies [7][8][9][10][11][12][13][14][15][16][17] and 8 comparative studies (including 2 metaanalyses) comparing CA methods (LCA vs PCA) or CA with other modalities [18][19][20][21][22][23][24][25]. Additional articles were included for assessment of long-term oncologic outcomes [26], functional results [27][28][29][30][31][32], salvage treatment options [33][34][35][36], and cost assessment [37][38][39].…”
mentioning
confidence: 99%
“…Dissections are difficult due to distortion of normal anatomical planes and a high rate of pleural injury ( 14 ). Karam et al recently evaluated the feasibility, safety and pathologic, radiologic and functional outcomes of salvage surgery after prior renal mass ablation therapy ( 15 ). They concluded that failed renal ablation therapy can be salvaged with partial or radical nephrectomy with good intermediate outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11 patients underwent partial nephrectomy and three underwent radical nephrectomy. One patient had a positive microscopic margin and four patients (29 %) had Clavien grade III complications [46]. Similarly, Jimenez et al published their results of 27 patients requiring salvage nephrectomy (n = 12) or partial nephrectomy (n = 15).…”
Section: Salvagementioning
confidence: 96%